Nanomechanical electro-optical modulator based on atomic heterostructures - P. A. Thomas; O. P. Marshall; F. J. Rodriguez; G. H. Auton; V. G. Kravets; D. Kundys; Y. Su; A. N. Grigorenko (Nature Communications, 2016)
Van der Waals heterostructures can be combined with metallic nanostructures to enable enhanced light–matter interaction. Here, the authors fabricate a broadband mechanical electro-optical modulator using a graphene/hexagonal boron nitride vertical heterojunction, suspended over a gold nanostripe array.